Jews in Sub-Saharan Africa: The case of South Africa, Nigeria, DR Congo and Ethiopia - Dirk Kohnert (Zenodo, 2024)
Jews in Africa have a long history. Africans have encountered Jewish myths and traditions in different forms and situations, leading to the development of a new Jewish identity linked to that of the Diaspora. Different groups of black Jews from western, central, eastern and southern Africa used and imagined their oral traditions and traditional practices to construct a distinct Jewish identity. In the early 20th century, two separate diasporas merged into an entirely new arena. Africans and African Americans adopted Judaism as a form of personal emancipation from colonial oppression and the effects of neo-colonialism. The adoption of Judaism by black Africans was a form of liberation from Anglo-Christian authority. Blacks and Jews are the two marginalised and stigmatised minorities in Western culture. Since ancient times they have maintained a complex relationship of identification, cooperation and rivalry. The Igbo of Nigeria, for example, were at the forefront of a normative Jewish movement that included several other ethnic groups. The rhetoric of the Holocaust, Zionism and the external features of Judaism were exploited by the Biafran neo-secessionists for their own ends. Furthermore, from the first mention of Africans in the Hebrew Bible to the contemporary demands of the Black Lives Matter movement, there has been support for the 'Palestinian resistance' but almost nothing that could have provoked a confrontation between blacks and Jews. The majority of African Jews live in South Africa. However, most of them are white. The South African Jewish community numbered more than 120,000 in the mid-1970s. After several large waves of emigration at the end of the apartheid regime, the number fell to just over 50,000. However, the Jewish claim to South African citizenship is controversial. The South African host society distinguishes between the Jewish diaspora and South African citizenship. Since the early 1990s, the second-largest Jewish community in sub-Saharan Africa has developed in Nigeria, which previously did not appear on any map of the Jewish world. Nine out of ten Nigerian Jews are Igbo. Estimates range from 3,000 to 30,000 Jews. Israel, however, refuses to recognise them as a Jewish population. In the DR Congo, a small Jewish community has held a special position since colonial times. Many Jews were among Leopold II's close advisers and agents in his Congo Free State (1885-1908). Jews also played an important role in Katanga Province in the 20th century, when the first mines were opened there and a railway line to South Africa was built. However, Mobutu's Zairisation (1973) and the looting of 1991 forced most Jewish entrepreneurs to leave the country. Ethiopia could be considered the cradle of Judaism, including the ancient kingdom of Sheba, mentioned in the Hebrew Bible and the Koran, and Beta Israel. Today, however, the harsh reality faced by Ethiopian Jewish immigrants in Israel reveals the racism that is deeply rooted in Israeli society. – – Juden in Afrika haben eine lange Geschichte. Afrikaner sind jüdischen Mythen und Traditionen in unterschiedlichen Formen und Situationen begegnet, was zur Entwicklung einer neuen jüdischen Identität geführt hat, die mit der der Diaspora verknüpft ist. Verschiedene Gruppen schwarzer Juden aus West-, Zentral-, Ost- und Südafrika nutzten und imaginierten ihre mündlichen Überlieferungen und traditionellen Praktiken, um eine eindeutige jüdische Identität aufzubauen. Ab dem frühen 20. Jahrhundert verschmolzen zwei getrennte Diasporas in einer völlig neuen Arena. Afrikaner und Afroamerikaner übernahmen das Judentum als eine Form der persönlichen Emanzipation von der kolonialen Unterdrückung und den Auswirkungen des Neokolonialismus. Die Übernahme des Judentums durch Schwarzafrikaner war eine Form der Befreiung von der anglo-christlichen Autorität. Schwarze und Juden sind in der westlichen Kultur die beiden marginalisierten und stigmatisierten Minderheiten. Seit der Antike pflegen sie ein komplexes Verhältnis zwischen Identifikation, Kooperation und Rivalität. Die Igbo von Nigeria beispielsweise standen an der Spitze einer normativen jüdischen Bewegung, die auch mehrere andere ethnische Gruppen umfasste. Die Holocaust-Rhetorik, Zionismus und die äußeren Merkmale des Judentums wurden von biafranischen Neo-Sezessionisten instrumentalisiert. Außerdem gab es, von der ersten Erwähnung von Afrikanern in der hebräischen Bibel bis zu den zeitgenössischen Forderungen der Black Lives Matter-Bewegung, Unterstützung für den ,,palästinensischen Widerstand“, aber fast nichts, was eine Konfrontation zwischen Schwarzen und Juden hätte provozieren können. Die meisten afrikanischen Juden leben in Südafrika. Allerdings sind die meisten von ihnen weiß. Die jüdische Gemeinde Südafrikas zählte Mitte der 1970er Jahre mehr als 120.000 Mitglieder. Nach mehreren großen Auswanderungswellen am Ende des Apartheidregimes sank sie auf knapp über 50.000. Der Anspruch jüdischer Personen auf südafrikanische Zugehörigkeit ist jedoch umstritten. Die südafrikanischen Aufnahmegesellschaft unterscheidet zwischen der jüdischen Diaspora und südafrikanische Zugehörigkeit. In Nigeria hat sich seit Anfang der 1990er Jahre die zweitgrößte jüdische Gemeinde in Subsahara Afrika entwickelt, die zuvor auf keiner Landkarte der jüdischen Welt auftauchte. Neun von zehn nigerianischen Juden sind Igbo. Schätzungen zählen 3.000 bis 30.000 Juden. Israel weigert sich allerdings, sie als jüdische Bevölkerung anzuerkennen. In der DR Kongo nimmt eine kleine jüdische Gemeinde seit der Kolonialzeit eine besondere Stellung ein. Viele Juden gehörten zu den engen Beratern Leopolds II. und den Agenten seines Freistaats Kongo (1885–1908). Juden spielten im 20. Jahrhundert auch eine wichtige Rolle in der Katanga-Provinz, seitdem dort die ersten Minen eröffnet und eine Eisenbahnlinie nach Südafrika gebaut wurde. Allerdings zwangen Mobutus Zairisierung (1973) und die Plünderungen im Jahr 1991 die meisten jüdischen Unternehmer, das Land zu verlassen. Äthiopien könnte als Wiege des Judentums betrachtet werden, einschließlich des alten Königreichs Saba, das in der hebräischen Bibel und im Koran erwähnt wird, ebenso wie Beta Israel. Heute jedoch offenbart die harte Realität, mit der äthiopisch-jüdische Einwanderer in Israel konfrontiert sind, den Rassismus, der tief in der israelischen Gesellschaft verwurzelt ist.
Keywords: F35; F52; F54; K37; N17; O15; O55; Z12; 330; Jewish identity; Jewish mythologie; Black Jews; Jewish diaspora; Beta Israel; Lemba people